Pengaruh Strategi Offline, Kualitas Pelayanan dan Kepercayaan Terhadap Keputusan Menjadi Nasabah Prioritas di Era Pandemi COVID-19 di Bank Jatim Malang (Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze the influence of Offline Marketing Strategy, Service Quality, and Trust on the Decision to Become a Priority Customer in the era of the COVID-19 pandemic at Bank Jatim Malang Branch. The research method is quantitative with a causal research approach to determine the relationship and influence between variables analyzed through multiple linear regression tests. The research sample consisted of 50 priority customers selected by purposive sampling technique. The results of the study show that simultaneously, the variables of Offline Marketing Strategy, Service Quality, and Trust have a significant influence on the decision to become a priority customer. Partially, Service Quality and Trust have a significant effect on customer decisions, while Offline Marketing Strategy does not have a significant individual influence. However, of the three variables, Offline Marketing Strategy has a dominant influence on the decision to become a customer, as evidenced by the largest Beta coefficient value. The conclusion of this study is that the combination of marketing strategy, service quality, and customer trust plays an important role in improving customer decisions to become a priority. Therefore, Bank Jatim can increase the effectiveness of offline marketing and strengthen services to increase customer satisfaction and loyalty.